2018
DOI: 10.1021/acs.jpcc.8b08623
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lone-Pair Surface States on Indium Oxide

Abstract: Indium oxide is widely used as a transparent electrode in optoelectronic devices and as a photocatalyst with activity for the reduction of CO 2 . However, very little is known 1 about its surface structure. In this report, directional lone-pair surface states due to filled 5s 2 orbitals have been identified on In 2 O 3 (111) through a combination of hard and soft X-ray photoemission spectroscopy and density functional theory calculations.The lone pairs reside on indium ad-atoms in a formal +1 oxidation state, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
1
12
0
1
Order By: Relevance
“…[330][331][332][333] In the last decade, In 2 O 3 itself has been rediscovered to be a wide-bandgap semiconductor with great potential and has received lots of attentions from the semiconductor physics community, 299 due to its fascinating structural, 334-337 mechanical [338][339][340] and electronic properties. [341][342][343][344] The explorations of the influence of defects on conductivity of In 2 O 3 has a long history. Bierwagen et al summarized the results of Hall mobility and Hall electron concentration in unintentionally doped, In 2 O 3 thin films and bulk samples and observed a qualitatively similar trend, that simultaneously increased in electron mobility and decreased electron concentration, consistent with O 2 annealing reduced donor concentration, as shown in Fig.…”
Section: Wide Bandgap Oxide Semiconductorsmentioning
confidence: 99%
“…[330][331][332][333] In the last decade, In 2 O 3 itself has been rediscovered to be a wide-bandgap semiconductor with great potential and has received lots of attentions from the semiconductor physics community, 299 due to its fascinating structural, 334-337 mechanical [338][339][340] and electronic properties. [341][342][343][344] The explorations of the influence of defects on conductivity of In 2 O 3 has a long history. Bierwagen et al summarized the results of Hall mobility and Hall electron concentration in unintentionally doped, In 2 O 3 thin films and bulk samples and observed a qualitatively similar trend, that simultaneously increased in electron mobility and decreased electron concentration, consistent with O 2 annealing reduced donor concentration, as shown in Fig.…”
Section: Wide Bandgap Oxide Semiconductorsmentioning
confidence: 99%
“…The microscopic origin of the surface 2DEG in In 2 O 3 has been attributed to surface concomitant V O s acting as doubly ionized shallow donors, [25b] and recently it was suggested that surface In adatoms which are more energetically favored over V O s, can also act as shallow donors. [63] The SEAL was also found to be sensitive to surface adsorbates. Oxidizing O 2 or NO 2 species lead to a decrease of the SEAL, while reducing conditions are prone to enhance it.…”
Section: Surface 2degmentioning
confidence: 99%
“…c) The calculated surface states of In ad-atoms and schematic for the 2DEG. Adapted with permission [63]. Copyright 2019, American Chemical Society.…”
mentioning
confidence: 99%
“…The microscopic origin of the SEAL has been further associated with surface oxygen vacancies [17] acting as doubly ionized shallow donors V 2+ O and their strongly reduced defect formation energy [18]. Finally, surface In adatoms, which are energetically favored over V O [19], can also act as shallow donors [20] and have been experimentally demonstrated on the In 2 O 3 (111) surface after a reducing surface preparation (annealing at 300 • C−500 • C in ultra-high vacuum (UHV)) [19].…”
Section: Introductionmentioning
confidence: 99%